Modeling automatic horizontation system of steep-sloping mobile machine with hydraulic sensor roll - V. I. Grishchenko; A. A. Tumakov; M. S. Poleshkin; M. S. Kilina; D. D. Dymochkin (Омский научный вестник)
The article is devoted to modeling the leveling system of a mobile machine using a hydraulic sensor that controls a hydromechanical system. The review of modern leveling systems for mobile machines made it possible to determine the criteria for assessing the quality of such systems and to prepare a circuit solution based on a membrane hydraulic sensor. The developed mathematical model made it possible to investigate the leveling process under changing conditions of operation of a steep-sloping mobile machine using the example of the «Don-1200K» combine. A generalized mathematical model of the leveling system with a submodel of the control roll sensor has been developed. A computational experiment is performed in the Matlab Simulink software environment based on the modules of the Simscape subroutine using numerical methods, which allowed to identify processes under varying loads on the chassis of mobile machine. The efficiency of the proposed solution is proved by the example of the hydromechanical system of the Don 1200 steep-slope combine, the working ranges of the hydromechanical leveling system and its dynamic qualities were determined. The found patterns reveal the dependencies of: angular and linear displacements of the leveling system; pressure changes in membrane chambers of the roll sensor; fluid flow through the throttle and the displacement of the control valve spool; loads on telescopic chassis hydraulic cylinders; speeds of movement of plungers of hydraulic cylinders of a leveling system. The results obtained can be used to upgrade existing mobile machines, as well as to create new steeply technological and transport machines with improved characteristics. Using the developed mathematical and computer models will reduce the time and cost involved in designing mobile equipment leveling systems, developing prototypes and commissioning.